Rhox8 Ablation in the Sertoli Cells Using a Tissue-Specific RNAi Approach Results in Impaired Male Fertility in Mice - Welborn, Joshua P. (Biol Reprod, 2015)
The reproductive homeobox X-linked, Rhox, genes encode transcription factors that are selectively expressed in reproductive tissues. While there are 33 Rhox genes in mice, only Rhox and Rhox8 are expressed in Sertoli cells, suggesting that they may regulate the expression of somatic-cell gene products crucial for germ cell development. We previously characterized Rhox5-null mice, which are subfertile, exhibiting excessive germ cell apoptosis and compromised sperm motility. To assess the role of Rhox8 in Sertoli cells, we used a tissue-specific RNAi approach to knockdown RHOX8 in vivo, in which the Rhox5 promoter was used to drive Rhox8-siRNA transgene expression in the postnatal Sertoli cells. Western and immunohistochemical analysis confirmed Sertoli-specific knockdown of RHOX8. However, other Sertoli markers, Gata1 and Rhox5, maintained normal expression patterns, suggesting that the knockdown was specific. Interestingly, male RHOX8-knockdown animals showed significantly reduced spermatogenic output, increased germ cell apoptosis, and compromised sperm motility, leading to impaired fertility. Importantly, our results revealed that while some RHOX5-dependent factors were also misregulated in Sertoli cells of RHOX8-knockdown animals, the majority were not, and novel putative RHOX8-regulated genes were identified. This suggests that while reduction in levels of RHOX5 and RHOX8 in Sertoli cells elicits similar phenotypes, these genes are not entirely redundant. Taken together, our study underscores the importance of Rhox genes in male fertility and suggests that Sertoli cell-specific expression of Rhox5 and Rhox8 is critical for complete male fertility.